Presentación: habitar lo religioso, negociar las normas, trazar los sentidos = Introduction : inhabiting the religious, negotiating the norms, tracing the meanings - Somoza, Mari-Sol García (Ciencias sociales y religión, 2019)
The texts gathered in this dossier refer incessantly to the question that relates the terms of agency and regulations. What we are trying to do here is present how breaking with normative judgments deepens the agency capacity. These manuscripts are the product of a previous discussion that took place within the Conference on Religious Alternatives in Latin America. The working group from which many of the discussions started was formed having as a principle a balance that represented authors from different disciplines and universities that make up the Association of Social Scientists of Religion of Mercosur and who work from Argentina, Brazil, Chile, Uruguay; as well as those other universities in France and Italy with which ties of dialogue and scientific exchange were established. Nine articles from the twelve initials make up a varied body whose theme is to think about gender, the construction of agencies, the provision of regulations and the condition of subalternities, not with the desire to return to old dilemmas but to problematize from other optical. Readers will find more consolidated works and others more incipient. This diversity accounts for the different paths of each researcher, but also for the difficulty of thinking about the regulations under less comfortable and less common analyzes.